Pengaruh Dimensi Supply Chain Management terhadap Keunggulan Bersaing pada UMKM Coffee Shop di Kota Semarang - Gabriella Audrey; Widiartanto Widiartanto; Andi Wijayanto (Universitas Diponegoro, 2022)
Competitive advantage has an important role for the sustainability of the company, where the company must be able to win the competition with its competitors in order to continue to run its business. Coffee shop in Semarang City is one of the businesses with intense competition, so every coffee shop owner must rack his brain to increase the competitive advantage of each business so that it does not go bankrupt. One of the factors that influence competitive advantage is the dimension of supply chain management which consists of strategic supplier partnerships, customer relationships, and information sharing. This type of research is explanative. Sampling using purposive sampling technique as many as 56 respondents who are owners or headbarista SMEs coffee shop in the city of Semarang. Collecting data using questionnaires, interviews, and literature study. This study uses quantitative analysis using validity, reliability, classical assumption test, correlation coefficient, coefficient of determination, simple and multiple linear regression, t test, and F test which is processed using SPSS (Statistical Program for Social Science) 26.0 version. The results showed that there was a positive and significant effect of supply chain management, customer relationship and information sharing variables, either partially or simultaneously, on the competitive advantage of MSME coffee shops in the city of Semarang. The higher the quality of supply chain management, customer relationship and information sharing, the higher the competitive advantage of coffee shop SMEs in Semarang City. Keunggulan bersaing saat ini memiliki peranan penting untuk keberlanjutan perusahaan, dimana perusahaan harus dapat memenangkan persaingan dengan para pesaingnya agar dapat terus menjalankan usahanya. Coffee shop di Kota Semarang merupakan salah satu usaha dengan persaingan yang ketat, sehingga setiap pemilik coffee shop harus memutar otak untuk meningkatkan keunggulan bersaing masing-masing usaha sehingga tidak mengalami kebangkrutan. Salah satu faktor yang mempengaruhi keunggulan bersaing adalah dimensi supply chain management yang terdiri dari strategic supplier partnership, customer relationship, dan information sharing. Tipe penelitian ini adalah eksplanatif. Pengambilan sampel menggunakan teknik purposive sampling sebanyak 56 responden yang merupakan pemilik atau headbarista UMKM coffee shop di Kota Semarang. Pengumpulan data menggunakan kuesioner, wawancara, dan studi pustaka. Penelitian ini menggunakan analisis kuantitatif dengan menggunakan uji validitas, reliabilitas, uji asumsi klasik, koefisien korelasi, koefisien determinasi, regresi linier sederhana dan berganda, uji t, dan uji F yang diolah menggunakan SPSS (Statistical Program for Social Science) 26.0 version. Hasil penelitian menunjukkan adanya pengaruh positif dan signifikan variabel supply chain management, customer relationship dan, information sharing baik secara parsial maupun simultan terhadap terhadap keunggulan bersaing pada UMKM coffee shop di Kota Semarang. Semakin tinggi kualitas pengelolaan supply chain management, customer relationship dan, information sharing, maka semakin meningkatkan keunggulan bersaing UMKM coffee shop di Kota Semarang.